Challenges in Implementing Subject Specialisation by Primary Teachers in Zimbabwe - Majoni, Cuthbert (IJRDO- Journal of Educational Research, 2016)
The study aimed at investigating challenges faced by teachers in implementing subject specialisation in primary schools in Zimbabwe. A case study design was used and primary schools in Bindura Primary Schools which have which apply subject specialisation were conveniently selected. Data were generated through interviews open-ended questionnaires. Data were qualitatively analysed. The study found out that there was more of subject sharing than subject specialisation since teachers were teaching subjects they did not specialise in. The study concluded that subject specialisation is relevant in primary school teaching and learning an appropriate model should be designed to ensure its effectiveness. The study recommended that an appropriate model be designed to ensure subject specialisation is applied effectively in schools.